Interspeech 2019 2019
DOI: 10.21437/interspeech.2019-2910
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Clinical Voice Parameters Captured with Smartphones — Measurements of Added Noise and Spectral Tilt

Abstract: Smartphones have become powerful tools for data capture due to their computational power, internet connectivity, high quality sensors and user-friendly interfaces. This also makes them attractive for the recording of voice data that can be analysed for clinical or other voice health purposes. This however requires detailed assessment of the reliability of voice parameters extracted from smartphone recordings. In a previous study we analysed reliability of measures of periodicity and periodicity deviation, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…These results are supported by the GRBAS results of this corpus as well: there is a notably smaller difference of perceived dysphonia between those with and without PD. Although the perceptual evaluation reveals a less distinguishable dysphonia, other factors could be influencing these results, such as the differences in microphones, background noise, and acoustic conditions in the mPower corpus collection method, as suggested in previous studies [64,65].…”
Section: Baseline Resultsmentioning
confidence: 75%
“…These results are supported by the GRBAS results of this corpus as well: there is a notably smaller difference of perceived dysphonia between those with and without PD. Although the perceptual evaluation reveals a less distinguishable dysphonia, other factors could be influencing these results, such as the differences in microphones, background noise, and acoustic conditions in the mPower corpus collection method, as suggested in previous studies [64,65].…”
Section: Baseline Resultsmentioning
confidence: 75%
“…All audio recordings were saved as WAV files. Unlike previous studies, we did not use professional recording hardware in order to maximize the potential telemedical applications of our results 23,24 …”
Section: Methodsmentioning
confidence: 99%
“…Authors concluded that smartphones could be used as a screening tool for voice disorders [ 15 ]. On the other hand, using some other acoustic voice quality parameters could be discouraging [ 16 ]. Two recent studies found that none of the studied smartphones could replace the professional microphone in a voice recording to evaluate the six parameters analyzed, except for f 0 and jitter.…”
Section: Introductionmentioning
confidence: 99%